ChemInform Abstract: Diastereoselective Synthesis of Novel Aza‐Diketopiperazines via a Domino Cyclohydrocarbonylation/Addition Process. Issue 4 (January 2015) - Regenass, Pierre; Margathe, Jean‐Francois; Mann, Andre; Suffert, Jean; Hibert, Marcel; Girard, Nicolas; Bonnet, Dominique
Abstract The stereoselective synthesis of novel bicyclic and tricyclic aza‐diketopiperazines is developed.